Competition and resilience: Lean manufacturing in the plastic industry in Lebanon - Abdallah Nassereddine; Ali Wehbe (Arab Economic and Business Journal, 2018)
In recent years, competition in the Lebanese plastic industry has significantly increased. At the same time, industry reports have shown that the sector is still resilient. A closer look at the sector shows that mounting competition incentivized many firms to adopt manufacturing systems that can provide better cost and quality. A large number of studies in the literature have focused on lean production and its efficiency gains. However, the challenges remain in the ability to implement the lean philosophy in manufacturing industries. This paper aims to explore the production system in the plastic manufacturing in Lebanon and shed the light on the implementation of the lean system and its related barriers. Based on the literature, a map of lean practices is drawn. A survey analysis using a sample of 20 factories is performed to explore the status of lean implementation in these organizations. The results indicate the existence of several barriers and challenges that prevent the Lebanese plastic manufacturing firms to implement lean practices. Firms suffer from a wide misconception of the lean system. Moreover, the results reveal that several firms use some aspects of lean manufacturing without realizing it. Keywords: Lean manufacturing system, Competition, Challenges and barriers, Plastic industry, Lebanon